Exposure to cold weather during a mass gathering in the Philippines - Allison E Gocotano; Fidelita D Dico; Neil R Calungsod; Julie L Hall; Megan L Counahan (The World Health Organization, 2015)
Abstract Problem The visit of Pope Francis to the Philippines in January 2015 coincided with a tropical storm. For security reasons, the only road in and out of the area was closed 14.5 hours before the Pope's arrival. This meant that people had to wait for many hours with little shelter at the site. Medical teams in the field reported high numbers of people with cold stress during the mass gathering. Approach To review the event from a public health perspective, we examined the consultations made by medical teams in the field and interviewed key stakeholders, focusing on cold stress as a public health risk. Local setting The key reason for the Pope's visit to Palo and Tacloban was the devastation caused in these cities by typhoon Haiyan in 2013. We estimated that the visit attracted 300 000 people. The medical teams were advised to consider cold stress risks two days before the event but no other measures were taken. Relevant changes Of the 1051 people seeking medical care, 231 people were experiencing symptoms of cold stress. People with cold stress ranged from 2 to 89 years of age and were more likely to be female than male, 173 (75%) versus 57 (25%). Lessons learnt Planning for mass gatherings should consider a wide range of public health risks, including cold stress. Improved data collection from the field is necessary to maximize the benefits of post-event evaluations and improve public health preparedness. Security measures to ensure the safety of key figures must be balanced with public health risks.